The effects of globalization and economic growth on income inequality: evidence for 24 OECD countries - Faustino, Horácio C.; Vali, Carim (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
Using the World Income Inequality Database and static and dynamic panel data analyses, this paper analyses the correlation between income inequality in the OECD countries and economic globalization, measured by trade openness and foreign direct investment, for the period 1995-2007. The static analysis, conducted by means of the fixed- effects estimator, suggests that trade openness reduces inequality, whereas FDI is positively linked to inequality. Some control variables, such as unemployment and inflation, also have a positive effect on inequality. When we control for endogeneity, using the system GMM estimator with the Windmeijer correction for small samples, the results also show that trade openness decreases income inequality and that the FDI effect on inequality is not significant. The country's economic growth causes inequality to increase, according to the findings of both our static and dynamic analyses. The Washington Consensus seems to be inconsistent
Argumenta Oeconomica, 2013, Nr 1 (30), s. 13-32
Keywords: globalization; economic growth; budget revenue; panel data; globalizacja; wzrost gospodarczy; dochody budżetowe; dane panelowe